Improvement proposal applying standardized work and 5's to reduce the rate of returned orders of a poultry company under the PDCA cycle - Silva Campusano, Danitza Alexandra (2023)
Over the last few years, the poultry sector has positioned itself advantageously in the Peruvian market since it contributes 56% of the animal protein consumption demanded by the population. This represents annual sales of around 11,000 million soles, which corresponds to 29% of the agricultural GDP. Based on the above, companies in this sector must be at the forefront to satisfy the growing demand of this product and avoiding customer dissatisfaction, since this reduces the profitability indexes generating economic loses. Part of these considerations is to reduce the 8.99% rate of order returns of a poultry company located in the south of Peru through a proposal that uses 5S tools and work standardization structured under the PDCA cycle. After the annual simulation of both models through the Arena software, the average error rate of the orders was reduced by 55.71%, the documentation search time by 44.04% and the order cycle time by 77.90%, all of them compared to their initial value. Resulting in a significant reduction to 4.95% of the order return rate.